Integration of children with disabilities into school community - Leliūgienė, Irena; Kaušylienė, Angelė (Social Welfare: Interdisciplinary Approach, 2012)
The article describes and defi nes socio-educational conditions of the integration of children with disabilities into school community. Appropriate integration may help to successfully solve social and education problems of children with disabilities, as well as achieve their equal rights and possibilities to participate in school community. The article theoretically presents the results of the research of socio-educational conditions of integrating children with disabilities into school community.